2008
DOI: 10.1177/1541204007305527
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Link Between Trauma and Delinquency

Abstract: The purpose of this study was to explore the influence of negative affect and delinquent peer exposure on the link between trauma and juvenile delinquency. Using a nationally representative sample of 2,065 males, a secondary data analysis was conducted to test a mediation model based on general strain theory. Mediation analyses revealed that negative affect (i.e., anger) and delinquent peer exposure exerted an intervening influence on the pathway between trauma and delinquency. These findings have important im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 83 publications
(103 reference statements)
2
35
0
Order By: Relevance
“…This study supports past researcher's findings (Ireland et al, 2002;Maschi et al, 2008;Stewart et al, 2008) and found that overall the frequency of childhood maltreatment predicts the frequency of later delinquent offending. In other words, the more frequently a child suffers maltreatment the more frequently he will commit delinquent offenses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study supports past researcher's findings (Ireland et al, 2002;Maschi et al, 2008;Stewart et al, 2008) and found that overall the frequency of childhood maltreatment predicts the frequency of later delinquent offending. In other words, the more frequently a child suffers maltreatment the more frequently he will commit delinquent offenses.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, childhood and adolescent maltreatment increases the likelihood that an individual will commit a delinquent act (Ireland et al, 2002;Maschi et al, 2008;Mersky & Reynolds, 2007); but, according to Zingraff et al (1993), this connection is weaker than previously supposed. Some researchers (Mersky & Reynolds, 2007;Widom & Maxfield, 1996) found that abuse and neglect are equally powerful in predicting delinquent violent and nonviolent offending.…”
Section: Physical Neglect As a Predictor Of Delinquency 233mentioning
confidence: 81%
“…We hypothesized that exposure to negative life events would predict increases in CU traits, which in turn would place youth at risk for experiencing future negative life events. Furthermore, because research has demonstrated that youth exposed to various negative life events (e.g., maltreatment, violence) manifest characteristics and behaviors associated with CU traits, such as conduct problems (e.g., Maschi, Bradley, & Morgen, 2008; CU TRAITS AND NEGATIVE LIFE EVENTS 6 Tiet et al, 2001), we controlled for co-occurring conduct problems in these analyses. While we acknowledge that some researchers view antisocial behavior as an integral part of psychopathy (e.g., Hare & Neumann, 2005), many theoretical models view it as a secondary characteristic that develops as a result of the core personality features (e.g., Skeem & Cooke, 2010).…”
Section: Present Studymentioning
confidence: 99%
“…The majority of the research exploring a causal link between traumatic experiences and adverse youth behavior has investigated the impact of child maltreatment before age 12 and its impact on maladaptive behavior, mostly among adolescent males (e.g., Lemmon 1999;Maschi 2006;Maschi et al 2008;Smith and Thornberry 1995). Other research studies that investigate the individual and social environmental risk factors for child maltreatment also have recognized that there may be a constellation of adverse consequences in the psychological, emotional, social, and behavioral domains among maltreated children that continue to impact them from adolescence into adulthood (e.g., Greenwald 2002;Jonson-Reid 1998;Margolin 1998;Wodarski et al 1990).…”
mentioning
confidence: 99%